The impact of wine yeast strains on the aromatic profiles of Sauvignon blanc wines derived from characterized viticultural treatments - Von Mollendorff, Anke (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScAgric)--Stellenbosch University, 2013.